Current status and trends of the world oil industry - Лютий, С.М.; Кочірко, Б.Ф.; Щербініна, Л.О. (Proceedings of National Aviation University (archive), 2009)
State-of-the-art and tendencies in the development of world refining industry have been considered. Information on capacities of the oil refining processes in the individual regions of the world, rating of the leading oil refining companies of the world, profitability indicators of huge oil companies as well as the data on catalysts used in oil refining processes are presented.